1995
DOI: 10.1182/blood.v85.1.283.bloodjournal851283
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of aplastic anemia in adults treated with antithymocyte globulin: comparison with bone marrow transplantation

Abstract: The outcome of 155 adult aplastic anemia (AA) patients treated with antithymocyte globulin (ATG, Upjohn, Kalamazoo, MI) at University of California, Los Angeles from 1977 to 1988 was evaluated. The median survival of the 146 patients who did not undergo bone marrow transplantation was 5.6 years, with 49% +/- 4% surviving more than 6 years. The most important predictor of survival was positive response to ATG (P < 0.001), which was observed in 48% of patients. Among pretreatment variables, disease severity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…ATG response criteria. The ATG response criteria were adopted from those used for assessing a response in AA (Paquette et al, 1995). Patients were evaluated at 3 and 6 months following ATG for haematological response.…”
Section: Methodsmentioning
confidence: 99%
“…ATG response criteria. The ATG response criteria were adopted from those used for assessing a response in AA (Paquette et al, 1995). Patients were evaluated at 3 and 6 months following ATG for haematological response.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies have shown that long-term survivors of aplastic anemia are at high risk for solid tumors as well as clonal hematological complications, such as paroxysmal nocturnal haemoglobinuria, myelodysplastic syndrome or acute myelogenous leukemia. [1][2][3][4][5] Focusing on solid tumors as late complications after aplastic anemia treatment, there are many reports of solid tumors developing after stem cell transplantation. [2][3][4][5][6][7][8] However, the development of solid tumors after IST is rare.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Focusing on solid tumors as late complications after aplastic anemia treatment, there are many reports of solid tumors developing after stem cell transplantation. [2][3][4][5][6][7][8] However, the development of solid tumors after IST is rare. The largest study from the European Group for Blood and Marrow Transplantation identified solid tumors in seven patients among 860 aplastic anemia patients treated with IST and in seven patients among 748 aplastic anemia patients treated with bone marrow transplantation (BMT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 With the improvement of (salvage) therapies in addition to supportive care measures, clinical outcomes in patients with AA have dramatically increased over the past four decades following IST or bone marrow transplantation (BMT) with an estimated 10-year survival rate of up to 80%. 7,8 Response rates (RRs) to IST vary according to different studies and the source of ATG. A hematologic recovery following front-line horse ATG-based IST (hATG) is seen in up to 60%-70% of patients, in comparison to 35%-45% in rabbit ATG (rATG)-treated patients with a significantly worse overall survival (OS), considering hATG as the first-line therapeutic option in AA.…”
mentioning
confidence: 99%